Development and Validation of an Instrument for Clinical Evaluation of Nursing Teachers (Student Form) in Ahvaz Jundishapur University of Medical Sciences Iran - Fahimeh Sabeti; Hossein Elhampour; Marzieh Shayestehfard; Soheila Sedaghat (Strides in Development of Medical Education, 2014)
Background & Objective: It is necessary for a correct evaluation to use valid instruments prepared exactly according to the study population and special field This study aimed to determine valid and reliable criteria for clinical evaluation of nursing teacher in Ahvaz Jundishapur University of Medical Sciences Iran   Methods: In this exploratorydescriptive study reviewing different sites and literature primary clinical evaluation form with 60 items based on the Likert scale was designed Face validity of the instrument was determined based on students teachers and nursing and educating professors opinions and content validity was determined based on Waltz and Bausell index Construct validity was determined by factor analysis Also reliability of instrument was determined by Cronbachs alpha coefficient splithalf coefficient and testretest   Results: Factor analysis to determine construct validity created two factors: educational behaviors factor with 21 phrases factor coefficient of 06330788 and eigenvalues of 20059 and supportive behaviors factor with 6 phrases factor coefficient of 06290799 and eigenvalues of 1915 Cronbachs alpha coefficient of clinical evaluation instrument was 095 totally 096 for factor 1 and 085 for factor 2 Splithalf coefficient was 081 and total Pearson correlation coefficient was 077 (P > 0001) Pearson correlation coefficient of answers to final question what do you evaluate your teacher finally? was 081 for factor 1 (P > 0001) and 072 for factor 2 (P > 0001)   Conclusion: Our instrument for clinical evaluation of nursing teachers (student form) was designed with two factors: educational behaviors factor with 21 phrases and suportive behaviors factor with 6 phrases and had a high degree of validity and reliability We suggest this instrument can be used for clinical evaluation of nursing teachers in Ahvaz Jundishapur University of Medical Sciences